Anticipatory Corticosteroid Administration to Asymptomatic Women with a Short Cervix - Richards, Douglas S.; Wong, Luchin F.; Esplin, M. Sean; Collingridge, Dave S. (American Journal of Perinatology, 2018)
Objective A short cervix is an important risk factor for spontaneous preterm birth. There is substantial evidence that antenatal exposure to corticosteroids significantly benefits infants that are born when delivery occurs between 24 and 34 weeks' gestation and after 48 hours but within 7 days of their administration. Our study was to evaluate whether asymptomatic women who are given a course of antenatal corticosteroids (ACS) at the time a short cervix is identified deliver within the window of proven steroid benefit.Study Design This was a retrospective chart review of patients who had a cervical length of < 2.5 cm between 23 and 34 weeks and who did not have cervical dilation or significant symptoms of preterm labor.Results Of 367 asymptomatic patients with a short cervix, only two (0.5%) delivered within 7 days of the time a short cervix was identified. With a policy of giving ACS at the time an ultrasound shows a short cervix, 184 patients would have to be treated for each one who realizes a steroid benefit by delivering within 7 days.Conclusion We conclude that unless future studies show that neonates benefit from ACS given more than 7 days before delivery, giving ACS to asymptomatic women solely because the cervix is short is not advised.
Keywords: antenatal corticosteroids; cervical length; premature birth